Decoding altitude-activated regulatory mechanisms occurring during apple peel ripening. (1st August 2020) - Karagiannis, Evangelos; Michailidis, Michail; Tanou, Georgia; Scossa, Federico; Sarrou, Eirini; Stamatakis, George; Samiotaki, Martina; Martens, Stefan; Fernie, Alisdair R; Molassiotis, Athanassios
Abstract: Apple ( Malus domestica Borkh) is an important fruit crop cultivated in a broad range of environmental conditions. Apple fruit ripening is a physiological process, whose molecular regulatory network response to different environments is still not sufficiently investigated and this is particularly true of the peel tissue. In this study, the influence of environmental conditions associated with low (20 m) and high (750 m) altitude on peel tissue ripening was assessed by physiological measurements combined with metabolomic and proteomic analyses during apple fruit development and ripening. Although apple fruit ripening was itself not affected by the different environmental conditions, several key color parameters, such as redness and color index, were notably induced by high altitude. Consistent with this observation, increased levels of anthocyanin and other phenolic compounds, including cyanidin- 3-O -galactoside, quercetin- 3-O -rhamnoside, quercetin- 3-O -rutinoside, and chlorogenic acid were identified in the peel of apple grown at high altitude. Moreover, the high-altitude environment was characterized by elevated abundance of various carbohydrates (e.g., arabinose, xylose, and sucrose) but decreased levels of glutamic acid and several related proteins, such as glycine hydroxymethyltransferase and glutamate–glyoxylate aminotransferase. Other processes affected by high altitude were the TCA cycle, the synthesis of oxidative/defense enzymes, and the accumulation of photosynthetic proteins. From the obtained data we were able to construct a metabolite-protein network depicting the impact of altitude on peel ripening. The combined analyses presented here provide new insights into physiological processes linking apple peel ripening with the prevailing environmental conditions.